Dispersion strategies for low-dimensional nanomaterials and their application in biopolymer implants. (August 2021) - Feng, P.; Kong, Y.; Liu, M.; Peng, S.; Shuai, C.
Abstract: Low-dimensional nanomaterials have great potential in enhancing mechanical properties of biopolymer implants due to their unique structure and properties. However, irreversible agglomeration of low-dimensional nanomaterials takes place spontaneously, which restricts their potential as reinforcement. In this study, dispersion strategies including surface modification, synergistic dispersion, and in situ growth for low-dimensional nanomaterials were summarized, and the specific dispersion mechanisms were emphatically discussed. To be specific, surface modification can form a thin coating film as physical barrier on the surface of low-dimensional nanomaterials through introduction of modifier, promoting their dispersion. Synergistic dispersion can construct a co-dispersion nanosystem via the co-supporting structures of two low-dimensional nanomaterials, thus increasing their space distance and weakening the interaction force to prevent their aggregation. In situ growth can achieve uniform synthesis of one low-dimensional nanomaterial on the surface of another, thus forming steric hindrance effect to prevent the aggregation. In addition, the techniques of incorporating low-dimensional nanomaterials into biopolymer were outlined, and the mechanical and biological properties of biopolymer reinforced with low-dimensional nanomaterials for various tissue engineering applications were also reviewed and discussed. Finally, suggestions for future study were presented, including the need for more investigations to assess the properties, and more in vivo and in vitro experiments before applications in tissue engineering.